Socio-economic complexities of smallholder resource-poor ruminant livestock production systems in Sub-saharan Africa. - Stroebel, A. (University of the Free State, 2004)
The challenge to overcome hunger remains one of the most serious confrontations facing humanity today. The threat of starvation is most serious in Africa, where an estimated 33% (138 million) of the population, mainly women and children, suffer from malnutrition. An estimated 680 million people, representing about two thirds of the rural poor, keep livestock, confirming the importance of livestock to their livelihoods. Understanding a live stock system requires description and analysis of its various components and their functional inter-relationships (the system’s functioning), rather than the description of livestock production alone. Therefore, the purpose of this study was to analyse the se relationships which are best understood by evaluating the various flows among system components as well as farmers’ management decisions. Farms vary in their resource endowments and in the family circumstances of the owners, with various resource flows and external interactions at the farm level. The biophysical, socio-economic and human elements of a farm are interdependent, and can be analysed as a system from various points of view. The challenges experienced in conducting diagnostic livestock studies are often attributed to the specific characteristics of livestock keeping. Taking cognisance of each farmer’s unique environment and context is central to the framework of farming systems research. No single component of smallholder farms in developing countries has as much potential as ruminant animals to address simultaneously the inter-related factors of under-nutrition, poverty and environmental decline that prevent people from improving their livelihoods. In mixed farming systems, as a result of the interplay among farm families, animals, crops and social systems, the roles and contributions of animals to smallholder agriculture are complex. The projected increased demand for livestock products could result in far-reaching changes in the structure of smallholder livestock production. Livestock never interact with natural resources in isolation, but people as livestock managers play a deciding role and are affected by biophysical, economic, social and policy factors. In this context, an integrated approach to natural resource management is required. Eighty-six smallholder cattle farmers in the Nzhelele District of the Limpopo Province of South Africa were surveyed. The farmers owned between one and 67 cattle, with an average of 10.3 head of cattle per household. The average age at first calving was 34.3 months. The rates of calving, weaning, calf mortality, herd mortality and offtake were 49.4%, 34.2%, 26.1%, 15.6% and 7.8% respectively. Contrary to the situation in many other regions of Southern Africa, commercial enterprise, not social prestige, constituted the main reason for farming with cattle. A marked complimentarity in resource-use i.e. crop residues as animal forage, has been demonstrated. Family size is the single most important factor among all variables studied (farm size, grazing land area, cultivated area and maize production area) that influences herd size for cattle and goats. The most important factor limiting the amount of land cultivated and the area used for maize production is farm size. Farm size has no relationship to the number of cattle or goats owned, as livestock predominantly depend on communal grazing. Animal traction supported by family labour, played a prominent role in land cultivation, due to the small farm size. Empirical studies and reviews from Eastern (Kenya) and Southern (South Africa) Africa has been used to construct a policy framework to guide livestock development in these two regions. Five overarching, integrated elements have been identified. These include food production and security, capacity strengthening for livestock research, livestock and the environment, health and genetics and marketing of livestock and livestock products. The framework that emerges is complex, due to the dramatically increasing demand for livestock products and, as a result, the farreaching changes in the structure of smallholder livestock production. To promote the development of smallholder farmers, different policy options must be assessed and evaluated, bearing in mind the farmers’ likely responses. New policies must include food production and security, capacity strengthening for livestock research, livestock and the environment, health and genetics and marketing of livestock and livestock products. An attempt has been made to translate these into complex, multi-disciplinary and multi-sectoral policy frameworks.